Współzarządzanie i partycypacja społeczna w rewitalizacji = Co-governance and social participation in revitalization - Przywojska, Justyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The statutory framework of revitalization in Poland clearly indicates that local cogovernance constitutes a context for the rehabilitation process. This primarily means using mechanisms and tools of revitalization that are based on engagement (participation) of citizens and other local actors. Such measures may be described as directed at the community, and their implementation should be preceded by a diagnosis of the participatory potential of the local community.
Keywords: partycypacja społeczna; współzarządzanie; rewitalizacja; ocial participation; co-governance; revitalization